2020
DOI: 10.2991/jegh.k.200417.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Low Back Pain in the Kingdom of Saudi Arabia: A Systematic Review

Abstract: The Kingdom of Saudi Arabia's (KSA) experience of rapid socioeconomic change, had given rise to new public health challenges and extensive health reforms [1-3]. The 2017 Lancet review of the prevalence of Low Back Pain (LBP) in the adult general population concluded that prevalence was greater in high-income countries (30%) than in low-income countries (18.2%) and more common in females than males [4]. Thus, LBP has been recognized by governments as a major public health issue and a serious challenge for healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 24 publications
2
23
3
Order By: Relevance
“…68.1% of flower farm workers of a study done in Kenya reported musculoskeletal discomfort [ 2 ]. In the Kingdom of Saudi Arabia (KSA), the prevalence of lower back pain in different professional groups within a working-age group ranges between 64% and 89% [ 7 ]. So as evidence suggests that the development of WMSD is almost inevitable for most workers, it is significantly associated with work organization factors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…68.1% of flower farm workers of a study done in Kenya reported musculoskeletal discomfort [ 2 ]. In the Kingdom of Saudi Arabia (KSA), the prevalence of lower back pain in different professional groups within a working-age group ranges between 64% and 89% [ 7 ]. So as evidence suggests that the development of WMSD is almost inevitable for most workers, it is significantly associated with work organization factors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Musculoskeletal disorders are the leading causes of loss of productivity and absenteeism of employees and affect quality of life [49,50]. The study found that the prevalence of low back pain among various groups of the Ethiopian working population ranged from 25.5% to 67.3%, which was lower than the nding of another study conducted in Saudi Arabia and found that the prevalence of lower back pain in different professional groups ranged from 64% to 89% [51]. Furthermore, the current found pooled prevalence of occupational-related low back pain accounted for 54.2% [95% of CI: 48.2, 60.0%], which was relatively lower than the pooled prevalence of low back pain in Africa, accounted for 57% [52].…”
Section: Discussionmentioning
confidence: 72%
“…Musculoskeletal disorders are the leading causes of loss of productivity and employee absenteeism and affect the quality of life [49,50]. The study found the prevalence of low back pain among various groups of the working population of Ethiopia ranged from 25.5-67.3% that was lower than the nding of another study conducted in Saudi Arabia and found the prevalence of lower back pain in different professional groups ranged from 64% and 89% [51].…”
Section: Discussionmentioning
confidence: 80%